Citation penalties following sexual versus scientific misconduct allegations. - Giulia Maimone; Gil Appel; Craig R M McKenzie; Ayelet Gneezy (PLoS ONE, 2025)
Background and aim Citations in academia have long been regarded as a fundamental means of acknowledging the contribution of past work and promoting scientific advancement. The aim of this paper was to investigate the impact that misconduct allegations made against scholars have on the citations of their work, comparing allegations of sexual misconduct (unrelated to the research merit) and allegations of scientific misconduct (directly related to the research merit). Methods We collected citation data from the Web of Science (WoS) in 2021, encompassing 31,941 publications from 172 accused and control scholars across 18 disciplines. We also conducted two studies: one on non-academics (N = 231) and one on academics (N = 240). Results The WoS data shows that scholars accused of sexual misconduct incur a significant citation decrease in the three years after the accusations become public, while we do not detect a significant citation decrease for scholars accused of scientific misconduct. The study involving non-academics suggests that individuals are more averse to sexual than to scientific misconduct. Finally, contrary to the WoS data findings, a sample of academics indicates they are more likely to cite scholars accused of sexual misconduct than those accused of scientific misconduct. Conclusions In the first three years after accusations became public, scholars accused of sexual misconduct incur a larger citation penalty than scholars accused of scientific misconduct. However, when asked to predict their citing behavior, scholars indicated the reverse pattern, suggesting they might mis-predict their behavior or be reluctant to disclose their preferences.